2015
DOI: 10.1016/j.virol.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and pathogenesis of a United States porcine deltacoronavirus cell culture isolate in 5-day-old neonatal piglets

Abstract: Porcine deltacoronavirus (PDCoV) was first identified in Hong Kong in 2009-2010 and reported in United States swine for the first time in February 2014. However, diagnostic tools other than polymerase chain reaction for PDCoV detection were lacking and Koch's postulates had not been fulfilled to confirm the pathogenic potential of PDCoV. In the present study, PDCoV peptide-specific rabbit antisera were developed and used in immunofluorescence and immunohistochemistry assays to assist PDCoV diagnostics. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
229
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(250 citation statements)
references
References 18 publications
17
229
0
4
Order By: Relevance
“…Previous studies have demonstrated that neonatal piglets are more susceptible than weaned pigs to PEDV infection, and PEDV infection induces greater disease severity in neonates than in weaned pigs (Jung et al, 2015a;Thomas et al, 2015). Therefore, a sensitive 5-day-old neonatal piglet model was selected for pathogenesis comparisons in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated that neonatal piglets are more susceptible than weaned pigs to PEDV infection, and PEDV infection induces greater disease severity in neonates than in weaned pigs (Jung et al, 2015a;Thomas et al, 2015). Therefore, a sensitive 5-day-old neonatal piglet model was selected for pathogenesis comparisons in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Five microlitres of each RNA template was used in a PCR setup in a 25 ml total reaction using the Path-ID Multiplex One-Step RT-PCR kit (Thermo Fisher Scientific). The primers, probes and in vitro-transcribed RNA used to generate standard curves of a quantitative PEDV N-gene-based real-time RT-PCR have been previously described (Lowe et al, 2014;Madson et al, 2014;Thomas et al, 2015). Based on standard curves, the virus concentration (expressed as genomic copies ml 21 ) in tested samples was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These clinical symptoms could lead to animal death. In general, PEDV and TGEV are considered more virulent than PDCoV (Chen et al, 2015), although after experimental inoculation of gnotobiotic piglets, PDCoV caused a severe disease (Jung et al, 2015b). Further analyses will be needed to determine whether the difference in viral strain, animal age, or other factors influence PDCoV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%